Factores relacionados e incidencia de la hemorragia postparto en gestantes del Hospital Martin Icaza de enero - agosto 2024. - De Loor Santana, Kelly Elizabeth (2024)
Postpartum hemorrhage is excessive bleeding after having experienced childbirth. The causes of postpartum hemorrhage may include loss of tone in the uterine muscles, hemorrhagic diseases, or retention or tearing of placental tissue, in the present work. This research aims to determine the related factors and the incidence of postpartum hemorrhage in pregnant women at the Martin Icaza Hospital during the period from January to August 2024, for which cross-sectional research was applied, it is observational in nature and analyzes data on variables collected in a period. of determined time, with a type of descriptive research that is responsible for specifying the characteristics of the population being studied, the method refers to two inverse intellectual processes that operate in unity: analysis and synthesis, while the modality is documentary for the compilation of the theoretical and field foundation for data collection through the survey, which was applied to 231 patients treated in the established period of time, obtaining as results that the related factors that most frequently affect The problems of postpartum hemorrhage in pregnant women are the age of the pregnant women, which mostly fluctuates between 20 and 35 years, uterine myomatosis and the fact of having suffered PPH in a previous pregnancy.